Morphological Characterization and Assessment of Genetic Variability of Tylenchulus semipenetrans Populations from Southern Iran - Rumiani Mohammad; Zouhar Miloslav; Karegar Akbar; Hamzehzarghani Habiballah; Tahmasebi Ahmad; Rashidifard Milad (Journal of Nematology)
Molecular data should be combined with morphological data to enhance the reliability of phylogenetic and diagnostic studies on nematodes. In this study, the citrus nematode Tylenchulus semipenetrans collected from citrus orchards in different localities in Fars province, southern Iran, was characterized using the partial sequencing of ITS rDNA, D2-D3 of 28S rDNA and COI mtDNA genes. We also morphometrically characterized the second-stage juveniles (J2) and male specimens. The results showed that T. semipenetrans is a genetically homogeneous species, and only minor nucleotide differences were detected among the populations. Phylogenetic studies demonstrated that most Iranian populations were grouped together, and there were no differences among the populations. However, sequence alignment of ITS, D2-D3 of 28S rDNA and COI mtDNA revealed 17, 24, and 16 single nucleotide variations (SNVs) and 11, 12, and 11 single-nucleotide polymorphisms (SNPs), respectively. The results of the morphometric analysis showed slight morphometric differences among and within the populations of T. semipenetrans. The morphometric differences among citrus nematode populations and the haplotype topology of the populations did not correlate with their geographical origin and host type. The constructed phylogenetic trees showed a close relationship between Tylenchulus and Trophotylenchulus. In addition, the phylogenetic relationships showed that T. musicola is the closest taxon to T. semipenetrans. The results of this study provide a better understanding of the diversity of T. semipenetrans populations and may shed light on the genetic variation of citrus nematode.